Analysis of the volcanic evolution of Nevado del Ruiz from the last eruptive period to the current state, using multispectral images provided by the group of satellites SENTINEL 1-2-3 (2019)
The analysis of satellite images produced by remote sensors, are a great tool for the identification of a range of ground cover and topsoil to the identification of particular lithologies and rock configurations regionally. The main objective is to evaluate the ability of Landsat and Sentinel satellites to define lithologies and types of volcanic flow and with them to carry out a hazard analysis. The particular features that are going to be analyzed correspond to: lava flows, lahars, ash, volcanic gases, volcanic rocks, erosion, snow, vegetation cover as well as other features such as slopes and water sources of the Nevado del Ruiz volcano. The information has been collected through an analysis that includes a multitemporal period from the last eruptive period to the present. In addition, images of past years to this last eruptive period were analyzed, where the peaks with the highest volcanic activity were recorded, in order to complement the results obtained. The justification for the acquisition of these results lies in creating volcanic geology mapping of ash, lava flows, pyroclasts, snow and lahars flows that clearly demonstrate the dangers that the volcano represents to nearby populations and avoid tragedies such as the one that happened in the municipality of Armero in the year of 1985.